Principles of esophageal cancer surgery, including surgical approaches and optimal node dissection (2- vs. 3-field) - Nafteux, Philippe (Ann Cardiothorac Surg, 2017)
Surgery for esophageal carcinoma and carcinoma of the gastro-esophageal junction (GEJ) is considered as one of the most complex and challenging interventions on the digestive tract. This is due to the intimate relations with vital structures in the chest and the tendency of early lymphatic dissemination via a dense and complex submucosal network. This review article discusses the different aspects of surgical access routes in the light of the ever-evolving techniques, in particular the minimally invasive esophagectomy (MIE). The aspects of surgical approach are inextricably linked to the still ongoing debate on extent of lymphadenectomy, a debate that is obtaining a new dimension in view of the widely applied neoadjuvant therapy protocols as well as in view of the increasing importance of quality of life aspects after surgery. Finally, the authors provide a practical and patient tailored approach as applied in their center.